Simulated Evolution and Learning 7th International Conference, SEAL 2008, Melbourne, Australia, December 7-10, 2008, Proceedings - Li, Xiaodong; Kirley, Michael; Zhang, Mengjie; Ciesielski, Vic; Michalewicz, Zbigniew; Hendtlass, Tim; Deb, Kalyanmoy; Tan, K. C.; Branke, Jürgen (Theoretical Computer Science and General Issues, 2008)
This volume constitutes the proceedings of the 7th International Conference on Simulated Evolution and Learning, SEAL 2008, held in Melbourne, Australia, during December 7-10, 2008. The 65 papers presented were carefully reviewed and selected from 140 submissions. The topics covered are evolutionary learning; evolutionary optimisation; hybrid learning; adaptive systems; theoretical issues in evolutionary computation; and real-world applications of evolutionary computation techniques.